Design of a Compact 900 MHz Class-F Power Amplifier with Efficiency Improvement using Modified Harmonic Control Circuit - Rasoul Azadi; Saeed Roshani; Arez Nosratpour; Mohammad Hazhir Mozaffari (Majlesi Journal of Electrical Engineering)
A Harmonic Control Circuit (HCC) is one of the most important blocks in the Class-F power amplifiers, which should pass the even harmonics and suppress the odd harmonics. Long open stubs are usually used to suppress odd harmonics in the conventional Class-F power amplifiers, which resulted in the large size of the amplifiers. In this work, two Class-F amplifiers are designed, a simple amplifier with traditional HCC and proposed PA with a proposed HCC. The proposed HCC suppresses third, fifth and seventh harmonics and easily pass second, fourth and sixth harmonics. In the proposed amplifier with proposed HCC, the design parameters are improved compared to the simple Class-F with traditional HCC. The power added efficiency (PAE), drain efficiency (DE) and gain parameters are increased from 76%, 79% and 19.4 dB to 79.2%, 82.2% and 21.2 dB, respectively. The proposed PA is fabricated, measured and results show that the proposed PA correctly works at 0.9 GHz with 0.12 GHz bandwidth.